The dilemmas of China`s market incomplete transformation ‒ the world economy perspective - Starzyk, Kazimierz (Dylematy niedokończonej transformacji chińskiej gospodarki z perspektywy gospodarki światowej, 2018)
The Chinese case suggests that the market transition is possible without a parallel transformation of the political system. The opposite case is that of Central European economies, where systemic political and institutional changes initiated the market transition processes. Thus, the Chinese pattern of transition can be called gradual, where the main objective is to build a market economy while keeping the single-party authoritarian political system. It bears fundamental implications upon the very process of market transformation making it gradual without a clear formulation of systemic goals at the outset of the process. The aim of the paper is to present the development problems faced by the Chinese economy now which solution determines the future position of China in the world economy. The text considers, among other things, the dilemma of authoritarian political system versus democracy, economic efficiency versus social justice and the challenges following the financial crisis 2007/8+.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 523, s. 392-399
Keywords: world economy; market transformation; open economy strategy; economic efficiency; crisis; China; gospodarka światowa; tranformacja rynkowa; strategia rozwoju otwartego; efektywność gospodarowania; fryzys finansowy; Chiny